The Perception and Attitude of Government Official on the Bilateral between Lao-China Initiatives under the Belt and Road Initiative (BRI) Case Study: Vientiane Capital : https://doi.org/10.69692/SUJMRD0802313 - CHANTHANASINH, Vadsana; KHAMPHENGVONG, Visansack; SOUKAVONG, Bounthone; VONGSAVANTHONG, Vonethaly; LAUNGPHONEXAY, Kimaneevan (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this study was to examine the level of perception and attitude of government officials on the bilateral between Lao-China Initiative under the Belt and Road Initiative (BRI). There are two methods of the study: the qualitative and methodology. The sample of this study comprised of government officials from 18 ministries with a total of 273 people. From querying the questionnaire, statistics analyze the data. The descriptive statistics include frequency, percentages, standard deviations, and binomial statistics to test the independent samples t -test, the One-way ANOVA. The results of this study show about knowledge and cooperation that are generally acknowledged and with perception on the attitude of the bilateral between Lao-China Initiative under the Belt and Road Initiative (BRI) about economic, trade and investment, social and economic, and issues and obstacles that are generally agreed upon. In addition, different individual factors, including age, level of education, the school, the experience of working, positions, and ministries (separate areas), will have different levels of perception of on the bilateral between Lao-China Initiative under the Belt and Road Initiative (BRI). Different, individual factors include having graduated from within the country and having the experience of working at different levels with different attitudes on the bilateral between Lao-China Initiative under the Belt and Road Initiative (BRI) with a statistical significance of 5 percentage.